Sex differences in clinical risk factors for Alzheimer's dementia patients with early-onset and late-onset - Faulstich, Nathan Gerhard; Hilmi Omar, Sammy; John O-brien, Connor; Ojo, Dami Taiwo; Brewer, Philip Cole; Nathaniel, Emmanuel I.; Goodwin, Richard; Roley, Laurie; Imeh-Nathaniel, Adebobola; Nathaniel, Thomas I. (Frontiers in Global Women's Health, 2025)
BackgroundThe objective of this study is to identify the risk factors that contribute to sex differences in patients with Alzheimer dementia (AD), specifically focusing on Early-Onset Alzheimer's Dementia (EAOD) and Late-Onset Alzheimer Dementia (LOAD). Additionally, the study aims to determine whether these risk factors differ between male and female EAOD and LOAD patients.MethodsOur retrospective cohort study included a total of 6,212 patients diagnosed with either EOAD or LOAD from February 2016 to August 2020. Among this population, 687 patients (11.06%) were diagnosed with EOAD, while 5,525 patients (88.94%) had LOAD. We conducted a univariate analysis to identify differences in risk factors between male and female AD patients. A multivariate analysis was also performed to predict specific risk factors associated with male and female EOAD and LOAD patients.ResultsIn the adjusted analysis, males with LOAD were found to have significantly higher odds of several comorbidities, including dyslipidemia [Odds Ratio (OR) = 1.720, 95% Confidence Interval (CI) = 1.489–1.987, p < 0.001], peripheral vascular disease (OR = 2.324, 95% CI = 1.828–2.955, p < 0.001), obstructive sleep apnea (OR = 2.330, 95% CI = 1.768–3.070, p < 0.001), and pneumonia (OR = 1.235, 95% CI = 1.004–1.520, p = 0.046). In contrast, females with LOAD were associated with lower odds of having hypertension (OR = 0.715, 95% CI = 0.623–0.820, p < 0.001), osteoporosis (OR = 0.310, 95% CI = 0.254–0.380, p < 0.001), urinary tract infections (OR = 0.638, 95% CI = 0.521–0.782, p < 0.001), congestive heart failure (OR = 0.626, 95% CI = 0.481–0.815, p < 0.001), and rheumatoid arthritis. In male patients with EAOD the analysis indicated a strong association with gait dysfunction (OR = 10.797, 95% CI = 3.257–35.792, p < 0.001), peripheral vascular disease (OR = 3.835, 95% CI = 1.767–8.321, p < 0.001), and Chronic Obstructive Pulmonary Disease (COPD) (OR = 5.984, 95% CI = 2.186–16.381, p < 0.001). Conversely, females with EOAD were associated with significantly lower odds of experiencing cerebrovascular accidents (OR = 0.347, 95% CI = 0.155–0.778, p < 0.001), osteoporosis (OR = 0.345, 95% CI = 0.155–0.778, p = 0.030), and anxiety (OR = 0.412, 95% CI = 0.203–0.833, p = 0.014).ConclusionsOur findings indicate sex differences in the risk factors for EAOD and LOAD patients. Understanding these risk factors can help us develop strategies to improve diagnostic accuracy, create targeted interventions, and enhance clinical outcomes for both male and female EAOD and LOAD patients.